2022
DOI: 10.1161/jaha.121.024449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sacubitril/Valsartan on the Right Ventricular Function and Pulmonary Hypertension in Patients With Heart Failure With Reduced Ejection Fraction: A Systematic Review and Meta‐Analysis of Observational Studies

Abstract: Background Sacubitril/valsartan (S/V) demonstrated significant effects in improving left ventricular performance and remodeling in patients with heart failure with reduced ejection fraction. However, its effects on the right ventricle remain unclear. This systematic review and meta‐analysis aimed to assess the impact of S/V on right ventricular function and pulmonary hypertension. Methods and Results We searched PubMed, Embase, Cochrane L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…To date, only Masarone et al in 215 patients with HFrEF [ 13 ], reported improvement in RV-pulmonary arterial coupling through the measurement of TAPSE/PASP ratio after 2 years of treatment with S/V, which was independent of left ventricular remodeling parameters. Therefore, although there is still no large evidence in the literature, our data support and confirm findings of available observational studies reporting the benefits of S/V on right heart function [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…To date, only Masarone et al in 215 patients with HFrEF [ 13 ], reported improvement in RV-pulmonary arterial coupling through the measurement of TAPSE/PASP ratio after 2 years of treatment with S/V, which was independent of left ventricular remodeling parameters. Therefore, although there is still no large evidence in the literature, our data support and confirm findings of available observational studies reporting the benefits of S/V on right heart function [ 30 ].…”
Section: Discussionsupporting
confidence: 90%
“…Invasive measurement also revealed a significantly reduced mean PCW at follow-up in patients with IpcPH [18 (15-23) mm Hg vs. 21 (18)(19)(20)(21)(22)(23)(24)(25)(26) mm Hg presacubitril/ valsartan, P , 0.01] (Fig. 1), whereas the reduction in mean PCW in patients with CpcPH was only tendential but not statistically significant [16 (10-25) mm Hg vs. 21 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) mm Hg presacubitril/valsartan, P = 0.09] (Fig. 2).…”
Section: Resultsmentioning
confidence: 91%
“…[12][13][14] Other studies have shown that sacubitril/valsartan reduces pulmonary pressure and improves right ventricular function in patients with heart failure with reduced ejection fraction, which does not seem to depend on reverse of left ventricular remodeling. [15][16][17][18] More recently, 2 small case series have shown that sacubitril/ valsartan also affects PAP in patients with HFpEF, suggesting an effect of sacubitril/valsartan on pulmonary hypertension independent of left ventricular function. 19,20 Therefore, we sought to investigate whether sacubitril/ valsartan affects pulmonary hypertension in a larger cohort of symptomatic patients with HFpEF.…”
Section: Introductionmentioning
confidence: 99%
“…These findings support the belief that there is a connection between LV and RV reverse remodeling in patients undergoing HF therapies which have been mainly attributed to LV dysfunction [ 76 ]. A systematic review and meta-analysis on the effect of S/V on the RV function in patients with HFrEF showed that RV systolic performance, evaluated by TAPSE and S’ wave velocity, improves after S/V treatment initiation [ 77 ]. Accordingly, not only LV function parameters, but also easily obtainable indices of RV function, such as TAPSE, S’ wave velocity, and RVFWLS should be measured when evaluating the response to treatment in HFrEF patients.…”
Section: Multi-modality Imaging Evaluation Of the Right Ventriclementioning
confidence: 99%